2013
DOI: 10.3400/avd.cr.13-00057
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Artery Aneurysm of the Hepatosplenomesenteric Trunk

Abstract: A splenic artery aneurysm is the most frequently observed visceral artery aneurysm, with an incidence of 40%-60% of all visceral aneurysms. [1][2][3] The most common treatment is surgical resection with or without splenic artery reconstruction, or exclusion with catheter intervention, which may reduce postoperative complications, such as pancreas injury. However, when the aneurysm is associated with an arterial anomaly, the treatment becomes complicated, especially if it is presented during pregnancy. We herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Since the first case reported by Ghatan et al 7 in 1967, only 46 cases of an anomalous SAA have been reported. 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 A summary of the reported cases is shown in the Table . The mean diameter was 32.5 mm, and 63% of the patients were women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first case reported by Ghatan et al 7 in 1967, only 46 cases of an anomalous SAA have been reported. 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 A summary of the reported cases is shown in the Table . The mean diameter was 32.5 mm, and 63% of the patients were women.…”
Section: Discussionmentioning
confidence: 99%
“…Open resection was performed in 25 cases and endovascular treatment in 16 cases (nine coils and seven stent grafts), with no reported complications or deaths. 4 , 5 , 6 , 7 , 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 Since the 2000s, endovascular treatment has been applied with increasing frequency. Although the long-term outcomes of stent graft placement at the SA remain unclear, the efficacy of endovascular treatment will be sufficient if the anatomic conditions are appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Mitsuru Tashiro 1) , Tsutomu Fujii 1) , Suguru Yamada 1) , Kojiro Suzuki 2) , Daishi Morimoto 1) , Nobutake Tanaka 1) , Hideki Takami 1) , Masamichi Hayashi 1) , Hiroyuki Sugimoto 1) and Yasuhiro Kodera We report a rare case of splenic aneurysm and splenic hamartoma with stricture of the celiac artery by median arcuate ligament compression. A 35-year-old man was found to have a splenic tumor on a medical examination.…”
Section: Splenic Aneurysm Near the Origin Of Splenic Artery And Splenmentioning
confidence: 93%
“…Thus, a hepatosplenomesenteric artery can be present in individuals with otherwise typical vasculature outside the superior aspect of the abdomen. Since the review of the literature by Chen et al [2] hepatosplenomesenteric trunks were reported in a patient undergoing surgery to repair a splenic artery aneurysm [7] and in a patient using computerized tomography. [8] A recently published cadaveric study describes a phrenicogastric trunk arising proximal to the hepatosplenomesenteric trunk, [9] as do we.…”
Section: Discussionmentioning
confidence: 99%